Building big - Macaulay, David (Boston : Houghton Mifflin, 2000)
A companion book to the PBS television series about the creation of bridges, tunnels, skyscrapers, domes, and dams, focusing on the connections between the main planning and design problems that had to be solved and the solutions that were ultimately constructed.
"Walter Lorraine books."
5.8
5-8
Keywords: Architecture -- Juvenile literature; Architecture; Architecture